A=(3x +4)(5x - 2) - (20x - 12)

B = 4 - 3x(2-5x)

Démontrer que A=B.

2
A= (8x +2) - (20x - 12)
= (-12x -10)
j'ai pas compris ta réponse !
y faut démontrer que les 2 c'est pareille pk tu dit sa toi t'est sur de ta réponse ?

Réponses

2014-04-05T14:11:25+02:00
A = (3x +4)(5x - 2) - (20x - 12)
=  15x² -6x + 20x - 8 - (20x - 12)
= 15x² + 12x - 8 -20x + 12
=  15x² - 6x + 4

B = 4 - 3x(2-5x)
= 4 - 6x + 15x²

A= B
  • Utilisateur Brainly
2014-04-05T14:14:10+02:00
A=(3x +4)(5x - 2) - (20x - 12)
  =15x²-6x+20x-8-20x+12
  =15x²-6x+4

B = 4 - 3x(2-5x)
   =4-6x+15x²
   =15x²-6x+4

donc A=B